Post-harvest practices and technology adoption in developing countries - Armah, Ralph Nii Armah (Kansas State University, 2019)
Study 1: Loss Aversion and Improved Storage Technology Adoption: Evidence from a Field Experiment in Ghana. Farmers in developing countries commonly sell the majority of their grain immediately after harvest, when prices are lowest. Improvements in technologies that reduce post-harvest losses (PHL) could potentially increase farm incomes by offering a more attractive means for farmers to save their output and sell at higher prices later in the season. This study examines how loss aversion affects the demand for one such technology, hermetically sealed bags, in a maize-growing region in Ghana’s Transition zone. Ignoring marketing decisions, loss aversion could potentially increase the willingness-to-pay (WTP) for improved storage technology because loss averse farmers may strongly desire to decrease grain losses. However, the possibility of selling one’s stock as a grain-loss averting strategy may flip the relationship between loss aversion and storage demand. If highly loss-averse individuals compensate for potential grain losses by immediate sales, improved storage technologies may not provide additional benefits. Using a Becker-Degroot-Marschak (BDM) auction for 386 farmers, the study finds support for the latter. Loss aversion is negatively related to WTP for hermetic bags, and this relationship is entirely driven by farmers whose grains sales occur soon after harvest. Nevertheless, despite limited previous experience with the bags and little access, a majority of farmers value hermetic storage bags at levels at or above market price prevailing in other parts of Ghana.   Study 2: Perceptions of Food Safety Risk, Post-harvest Practices and Intertemporal Staple Crop Allocation: Evidence from Maize in Nepal. Improving food safety is essential for improving food security: i.e. access to sufficient and healthy food. Unsafe food contains hazardous agents or contaminants (e.g. mycotoxins) that can increase people’s risk of chronic diseases; and may have considerable economic implications for developing-country markets due to losses for rejected marketable surpluses and lower prices for inferior quality crops. This study addresses two research questions: Do perceptions of food safety risk alter intertemporal allocation of staple crops? If so, is the change in the intertemporal allocation through the better post-harvest practices? Using a two-round panel data of 320 maize farmers in Nepal, this study finds that farm households who perceive themselves to have better awareness of food safety risks tend to store produced maize longer than the other households. However, there are no statistical differences in post-harvest practices between the households with higher perceived-awareness and the others. The findings imply that providing farmers with food safety information may enhance storage behavior for optimal intertemporal maize allocation. This requires strengthening the research-extension link to provide agricultural extension officers and farmers information on better post-harvest management and the provision of feedback for improved future research.
Keywords: Post-harvest loss; Improved storage technology; Willingness-to-pay; Loss aversion; Food safety awareness; Post-harvest practices